SPATIAL DISTRIBUTION OF INSALUBRITY WITHIN THE CITY OF COTONOU - HOUNKPONOU, MURIELLE KAYIVI ELIANE EPSE AMOUSSOU-GUENOU; AZONHE, S. Hervé Thierry; Agbossou, K.E (My University, 2019)
The fundamental objective of this research is to provide a better understanding of what causes insalubrity within the city of Cotonou. The probabilist method and the random choice technique have been used in the selection of the sample proportionally to the size of the structures based on some criteria. The sample’s size is determined in accordance with Schwartz method. In order to identify the causes of insalubrity, the parameters were introduced in the mini tab software to perform the simple regression analysis. The Durbin-Watson’s statistic, Ryan Joyner normality and Henri adjustment were used to assess the significance of the model. The evaluation study of healthy places is conducted through factors such as : rain water evacuation network, flood and coverage rate of pre-collection in order to determine a healh card. The combination of the factors of safety of the spaces is realized. It was calculated, the insalubrity rate (IS1) taking into account the effects of anthropogenic factors (rain water evacuation network coverage rate of pre-collection and volume of waste) on the salubrity. The regression analysis reveals that the increase of suscription fees by pre collection structures, the availability of empty spaces in urban districts, the setting up of waste gathering points in towns justify the rise of insalubrity rate in the urban areas studied. Moreover, an increase in the frequency of household solid waste collection (MSW) in households, reduces the suscription rate and compels households to discharge solid wastes in empty spaces in their neighborhoods or refer to the gathering points that are poorly maintained and rarely emptied
Keywords: Insalubrity; waste; management; Cotonou; Benin.